Potensi budidaya lebah madu sebagai harapan di tengah pandemi Covid-19 - Andhika Silva Yunianto; Syasri Jannetta (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2020)
More than three-quarters of Indonesia population depend on forest products, both timber and non-timber. Having not paying attention to sustainable forest management is believed to be the cause of forest damage getting worse in every year. COVID-19 made many people lose their livelihoods. If not anticipated, the remaining forest will suffer more damaged due to economic pressure forcing by communities around the area to doing deforestation. Honey bee cultivation is an alternative way of livelihoods for communities around forest areas. This is supported by the very high national scale demand for honey, but it is very inversely proportional with the low production of honey. The results showed that it is possible to cultivate Trigona Sp. bees in residential areas, buffer zone and traditional zone, so that it can be used as alternative source of income for the surrounding community, while preserving the environmental ecosystem. Within 4 months, honey yields from residential areas are 1.75 liters from 10 colonies, in the buffer zone as much as 4.3 liters from 13 colonies, and in the traditional zone as much as 10.65 liters from 44 colonies. Revitalization needs to be carried out in the buffer zone to provide additional protection for the area and benefit the community.